Results of human papillomavirus testing on self-collected versus clinician-collected samples - T E Belokrinitskaya; N I Frolova; O V Turanova; V A Pletneva; K N Shemyakina; N B Sambueva; E E Maltseva (IP Berlin A.V., 2017)
Objective - to evaluate the prevalence of high-risk human papillomavirus infection (HR HPV), the efficiency and acceptability on self-collected using the Qvintip device versus clinician-collected samples in vaginal discharge. Subjects and methods. A cross-sectional study involving 200 women attituded to an employer's outpatient clinic for periodic/annual medical examination. The mean age of the patients was 32.7±6.9 (range: 18-45 years). Vaginal discharge was collected using a Qvintip device and vaginal smear from the cervical canal was taken by a physician for a further HR HPV PCR test. A face-to-face interviews using to assess acceptability of the compared methods. Patients evaluated comfort, pain, privacy and embarrassment using the rating «yes» or «no». Results. 42% of all patients were HR HPV positive. The efficiency of the survey using the self-collected Qvintip device was higher than the clinician-taken samples: 38% vs 27.5% (OR=1.6; pχ2=0.025). The use of the Qvintip device only increased a chance to detect HR-HPV by 5 times: 36.3% vs 9.5% (OR=5.0; pχ2=0.0001). HPV-16 was the most frequently encountered HPV type (17.7%), followed by HPV-56 (16.3%), HPV-39 (13.6%), HPV-31 (10.9%), HPV-33 and HPV-51 (8.2%), HPV-58 (7.5%), HPV-52 (6.1%); HPV-45 (5.4%), HPV-18 (4.1%); HPV-35 (1.4%), HPV-59 (0.7%). 51.2% of HPV-positive women were infected with several types of HR HPV. Two types of HR HPV were detected in 34.5%, three - in 9.5%, four - in 6%, five - in 1.2 % patients. Self-sampling using the Qvintip device was a well-accepted method. Compared to physician-sampling, women reported a preference for self-sampling (64%), as it was more comfortable (75% vs 22.2%, p